PENGARUH PARTISIPASI ANGGARAN, PENEKANAN ANGGARAN DAN ASIMETRI INFORMASI TERHADAP BUDGETARY SLACK DENGAN KETIDAKPASTIAN LINGKUNGAN SEBAGAI VARIABLE MODERASI (Studi Empiris Pada OPD Kabupaten Kampar Tahun 2018) - Ferly Bitlinandas; Kamaliah Kamaliah; Susilatri Susilatri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine the effect of Budgetary Participation, Budget Emphasis and Information Asymmetry on Budgetary Slack with Environmental Uncertainty as Moderation Variable. The population of this research are all of OPD in Kampar Regency consisting 32 OPD. This study uses primary data in the form of questionnaires in Kampar District. Tests using SPSS 17.0 software. The result of coefficient of determination test shows that 94.9% Budgetary slack is influenced by budget participation, budget emphasis, information asymmetry and environmental uncertainty. The remaining 5.1% are influenced by other variables. The findings in this study are: Budget Participation has significant effect on Budgetary Slack. Budget emphasis has significant effect on Budgetary Slack. Information asymmetry has a significant effect on Budgetary Slack. Budget Participation on Budgetary Slack with Environmental Uncertainty as the moderation variable in this research is accepted. Budget Emphasis on Budgetary Slack with Environmental Uncertainty as a moderating variable in this study was accepted. Asymmetry Information on Budgetary Slack with Environmental Uncertainty as a moderating variable in this study was received.Keywords : Budgetary Slack, Budget Participation, Budget Emphasis, Information Asymmetry, and Environmental Uncertainty